A tryptophan metabolite prevents depletion of circulating endothelial progenitor cells in systemic low-grade inflammation - Mannarino, Massimo R.; Bianconi, Vanessa; Scalisi, Giulia; Franceschini, Luca; Manni, Giorgia; Cucci, Alessia; Bagaglia, Francesco; Mencarelli, Giulia; Giglioni, Francesco; Ricciuti, Doriana; Figorilli, Filippo; Pieroni, Benedetta; et al. (Frontiers in Immunology, 2023)
Chronic systemic inflammation reduces the bioavailability of circulating endothelial progenitor cells (EPCs). Indoleamine 2,3-dioxygenase 1 (IDO1), a key enzyme of immune tolerance catalyzing the initial step of tryptophan degradation along the so-called L-kynurenine (L-kyn) pathway, that is induced by inflammatory stimuli and exerts anti-inflammatory effects. A specific relationship between IDO1 activity and circulating EPC numbers has not yet been investigated. In this study, circulating EPCs were examined in mice treated with low doses of lipopolysaccharide (LPS) to mimic low-grade inflammation. Moreover, the association between IDO1 activity and circulating EPCs was studied in a cohort of 277 patients with variable systemic low-grade inflammation. Repeated low doses of LPS caused a decrease in circulating EPCs and L-kyn supplementation, mimicking IDO1 activation, significantly increased EPC numbers under homeostatic conditions preventing EPC decline in low-grade endotoxemia. Accordingly, in patients with variable systemic low-grade inflammation, there was a significant interaction between IDO1 activity and high-sensitivity C-reactive protein (hs-CRP) in predicting circulating EPCs, with low hs-CRP at high IDO1 activity associated with significantly higher EPCs but not at low IDO1 activity. Overall, these findings demonstrate that systemic low-grade inflammation reduces circulating EPCs. However, high IDO1 activity and L-kyn supplementation limit circulating EPC loss in low-grade inflammation.